Baseline nutritional status is prognostic factor after definitive radiochemotherapy for esophageal cancer. Issue 6 (26th October 2012) - Clavier, J.‐B.; Antoni, D.; Atlani, D.; Ben Abdelghani, M.; Schumacher, C.; Dufour, P.; Kurtz, J.‐E.; Noel, G.
Summary Identify prognostic factors for survival and patterns of treatment failure after definitive radiochemotherapy for esophageal cancer. Between 2003 and 2006, 143 patients with squamous cell carcinoma and adenocarcinoma of the esophagus were retrospectively reviewed. Median age was 65 years (42–81). Median radiation dose was 62.5 Gy (38–72) with 1.8–2 Gy fraction. Median follow‐up was 20.8 months (2.8–92.4). Three and 5‐year local recurrence‐free survival rates were 58.3% and 50.9%. In univariate analysis, traversable esophageal stricture was a prognostic factor. Three, 5‐year locoregional recurrence‐free survival rates were 42.4% and 34.9%. In multivariate analysis, traversable esophageal stricture and stage < IIB were independent prognostic factors. Three and 5‐year disease‐free survival rates were 30.5% and 25.9%. In multivariate analysis, Nutritional Risk Index (NRI) ≥ 97.5 and performance status (PS) = 0 were independent prognostic factors. Median, 3, and 5‐year overall survival rates were 22.1 months, 34.4%, and 19.8%. In multivariate analysis, independent prognostic factors were NRI ≥ 97.5 and PS = 0. Median survival times for the NRI classes (no denutrition, moderate and severe denutrition) were 29.5, 19.7, and 12 months (P = 0.0004), respectively. A major impact of baseline NRI was found in terms of survival; it should be included in future prospective trials.